Subjective Welfare, Isolation, and Relative Consumption - Fafchamps, Marcel (2012)
The recent literature has shown that subjective welfare depends on relative income. Much of the existing evidence comes from developed economies. What remains unclear is whether this is a universal human trait or an artifact of a prosperous, market-oriented lifestyle. Using data from Nepal, a mountainous country where many households still live in relative isolation, we test whether poorer and more isolated households care less about relative consumption. We find that they do not. We investigate possible reasons for this. We reject that it is due to parental concerns regarding the marriage prospects of their children. But we find evidence in support of the reference point hypothesis put forth by psychologists: household heads having migrated out of their birth district still judge the adequacy of their consumption in comparison with households in their district of origin.